DEVELOPMENT OF THE CONCRETE COVERAGES REPAIR TECHNOLOGY OF TRANSPORT BUILDINGS IN CONDITION OF GLOBAL WARMING (Transport systems and technologies, 2018)
The article provides information on the method of repairing concrete and reinforced concrete structures using a resin-based mineral composition that provides high adhesion to old concrete. The proposed method and polymer composition for the restoration of concrete pavement structures increased water resistance, frost resistance and water resistance, there is a significant increase in adhesive strength for dry, wet and water-saturated concrete. It provides reliable protection of concrete structures and coatings. A technique has been developed for repairing the surface layer of cement-concrete road pavements. The optimal composition of the compound was selected, which provides the lowest content of polymeric high physical and mechanical characteristics of the obtained coatings. The technological schemes for repairing the surface of cement-concrete coatings with polymer-mineral compositions are developed.
Keywords: repair; concrete; mineral composition; frost-resistance; watertightness